El Niño impacts in the Limpopo River Basin - Montes, Carlo (CGIAR System Organization, 2023)
Higher-than-average temperatures are predicted for the Limpopo Basin from June to November 2023. A delay in the onset of the rainy season in November is predicted. A reduction in rainfall and higher temperatures induced by the 2023 strong El Niño event are expected for the Limpopo Basin from January to March 2024. Historic data suggests a negative impact of El Niño on maize yields of the following season in South Africa, Mozambique and Zimbabwe.